Mathhelp346
HELP PLEASE!!!:
f(x)=3x-4
g(x)=-x^2
1.(f o g)(-2)
2.(f o f)(-2)
f(x)=2x
g(x)=x^2+2
h(x)=-4x+3
1.(h o f)o g
Delete
Share
This Question is Closed
Mathhelp346
Best Response
You've already chosen the best response.
0
for the first part, what does the 2 do? i know how to solve (f o g)(x)
micahwood50
Best Response
You've already chosen the best response.
1
(f o f)(-2) is basically saying f( f(-2) ), in other words, in 3x-4, replace x with ( 3x - 4 )
so you get f o f(-2) = 3( 3(-2) - 4 ) - 4 then simplify.
Mathhelp346
Best Response
You've already chosen the best response.
0
Oh ok
Mathhelp346
Best Response
You've already chosen the best response.
0
and how would i do the second part?
Mathhelp346
Best Response
You've already chosen the best response.
0
like h(f(x)(g(x))? but then how do i solve it
micahwood50
Best Response
You've already chosen the best response.
1
(h o f)(x) = h(f(x)) so (h o f)o g = h(f(x)) o g = h( f ( g(x) ) )
f(g(x)) = 2(x^2+2) so h ( f ( g ( x ) ) ) = -4(2(x^2+2) )+3
Is this clear enough?
Mathhelp346
Best Response
You've already chosen the best response.
0
yes thank you
micahwood50
Best Response
You've already chosen the best response.
1
Glad I helped.
Mathhelp346
Best Response
You've already chosen the best response.
0
wait but if f o g would nt it be h(f(x)(g(x))
Mathhelp346
Best Response
You've already chosen the best response.
0
h o f is h(f(x)) and then there's o g so wouldnt it be h(f(x)(g(x))
micahwood50
Best Response
You've already chosen the best response.
1
Well, h o f o g = h( f( g(x) ) )
Basically (h o f) o g is same since h and f go first anyway.
Mathhelp346
Best Response
You've already chosen the best response.
0
ah ok thanks